PLC ANALOGUE CONTROLLER FOR A BATCH PLANT - Wan Husin, Wan Saladiwiyana (Universiti Teknologi Petronas, 2006)
This report addresses the approach of designing and implementing the logic control functions for a batch process. The aim is to develop the controller for a batch process using PLC. Batch process involves sequential processing that leads to the production of finite quantities of material by subjecting quantities of input materials to an ordered set of processing activities over a finite period of time, using one or more pieces of equipment. Batch process can be classified as a discontinuous process. Liquid soap making is chosen as the case study for the project. The CX-Programmer programming software was used to develop the ladder diagram for the PLC, implementing the batch control. The concept of controlling a control system involves a systematic approach, and the operation procedure includes the determination of the machine sequence, inputs and outputs addressing, and the PLC programming. Troubleshooting is conducted to ensure that the program run in accordance to the intended process sequences and give the desired response of the control valves, the final control elements connected to the PLC. This approach is found to be effective in designing a logic ladder diagram for a PLC to control a batch process, in this case a liquid soap making process. in